(NpSIHOLOGIQ USWOENIQ ORFOGRAFII (B/s - (NbOGOQWLENSKIJ(B, (NdMITRIJ nIKOLAEWI^s 1898-1981 ((NmOSKWA (B:s (NiZD(B-(NWO apn (B,s, 1957)
(NaKADEMIQ pED(B. (NNAUK rsfsr(B. (NiNSTITUT pSIHOLOGIIs
Keywords: (NpSIHOLOGIQs